A Novel Recombinant Enterovirus Type EV-A89 with Low Epidemic Strength in Xinjiang, China - Fan, Qin; Zhang, Yong; Hu, Lan; Sun, Qiang; Cui, Hui; Yan, Dongmei; Sikandaner, Huerxidan; Tang, Haishu; Wang, Dongyan; Zhu, Zhen; Zhu, Shuangli; Xu, Wenbo (Scientific reports, 2015)
Enterovirus A89 (EV-A89) is a novel member of the EV-A species. To date, only one full-length genome sequence (the prototype strain) has been published. Here, we report the molecular identification and genomic characterization of a Chinese EV-A89 strain, KSYPH-TRMH22F/XJ/CHN/2011, isolated in 2011 from a contact of an acute flaccid paralysis (AFP) patient during AFP case surveillance in Xinjiang China. This was the first report of EV-A89 in China. The VP1 coding sequence of this strain demonstrated 93.2% nucleotide and 99.3% amino acid identity with the EV-A89 prototype strain. In the P2 and P3 regions, the Chinese EV-A89 strain demonstrated markedly higher identity than the prototype strains of EV-A76, EV-A90 and EV-A91, indicating that one or more recombination events between EV-A89 and these EV-A types might have occurred. Long-term evolution of these EV types originated from the same ancestor provides the spatial and temporal circumstances for recombination to occur. An antibody sero-prevalence survey against EV-A89 in two Xinjiang prefectures demonstrated low positive rates and low titres of EV-A89 neutralization antibody, suggesting limited range of transmission and exposure to the population. This study provides a solid foundation for further studies on the biological and pathogenic properties of EV-A89.